2020
DOI: 10.3390/atmos11101085
|View full text |Cite
|
Sign up to set email alerts
|

Complex Characterization of Fine Fraction and Source Contribution to PM2.5 Mass at an Urban Area in Central Europe

Abstract: It is well documented that Southern Poland is one of the most polluted areas in Europe due to the highest airborne concentrations of particulate matter (PM). Concentrations of fine particles are especially high in winter. Apart from detailed number concentrations, it is essential to accurately identify and quantify specific particulate pollution sources. Only a few Polish research centers are involved in such experiments—among them is Krakow research group. For the most part, research focuses on collecting 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It should be noted that during the periods of low temperatures, exceeded permissible or recommended pollutant concentrations were identified in all locations investigated under the present project. It was concluded that the most important factors determining the air quality in the study area involved burning poor-quality fuels in stoves for heating purposes (coal-fired boilers, fireplaces, and tiled and cooking stoves) [60][61][62]. That issue is especially important in health resorts, where air quality is one of the most important factors influencing their therapeutic value [63].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that during the periods of low temperatures, exceeded permissible or recommended pollutant concentrations were identified in all locations investigated under the present project. It was concluded that the most important factors determining the air quality in the study area involved burning poor-quality fuels in stoves for heating purposes (coal-fired boilers, fireplaces, and tiled and cooking stoves) [60][61][62]. That issue is especially important in health resorts, where air quality is one of the most important factors influencing their therapeutic value [63].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate sources of particulate matter in Krakow receptor model positive matrix factorization (PMF) was used. Such studies were performed for PM 2.5 fraction for the whole years 2016/2017 and 2018/2019 for the AGH station by Samek et al 6 , 7 . In the study 6 four factors were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Non-identified source contributed 8.2% to PM 2.5 mass. In the study 7 also four factors were obtained from PMF analysis. They were attributed to the following sources: soil, traffic/industry, fossil fuel combustion and secondary inorganic aerosols (SIA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential to identify accurately and quantify specific air particulate matter pollution by the BB aerosol, especially in the urban areas. In situ PM concentration measurements are common technique to estimate the air pollution in different regions of the globe [10][11][12][13], particularly using low-cost instruments for the air quality monitoring networks [14,15]. Also the remote sensing measurements are used for it [16][17][18][19], modeling [20,12] and synergy of different techniques [21].…”
Section: Introductionmentioning
confidence: 99%